(untitled) (UNIZIK Journal of STM Education, 2025)
The researchers delved into the Perception of Science Education Students on the Availability and Usability of Technological tools in Teaching and learning at Nnamdi Azikiwe University Awka in the era of Insecurity and Economic Meltdown. Descriptive survey research design was employed in the study. The study was guided by four research questions. The population of the study was consisted of nine hundred and eighty-six (986) undergraduate regular students in the Department of Science Education. The sample for the study consisted of one hundred and twenty (120) students chosen using stratified sampling technique. The instrument for data collection was questionnaire titled Availability and Usability of Teaching and Learning Technological Tools (AUTLTT). The AUTLTT was validated by three experts from Faculty of Education in Nnamdi Azikiwe University Awka. The reliability of the instrument was established using Cronbach Alpha Reliability technique given a reliability coefficient of 0.78 The data were analysed using Mean Score. The findings revealed among others that majority of the technological tools are not available in teaching and learning of Science Education courses. Many challenges such as inadequate and lack of access to the technological tools, poor and epileptic power supply/ internet access, lack of trained personnel among others face the use of technology in teaching and learning of Science Education courses. The researchers equally made recommendation of funding both the Science Education Department and other servicing Departments for procurement of technological tools for effective teaching and learning. The University internet provider and power supply should equally be upgraded. In-service training for the use of these tools was also recommended among others by the researchers.